Field experiment confirms high macroplastic trapping efficiency of wood jams in a mountain river channel - Maciej Liro; Paweł Mikuś; Anna Zielonka (Scientific Reports)
Abstract Identifying macroplastic deposition hotspots in rivers is essential for planning cleanup efforts and assessing the risks to aquatic life and the aesthetic value of river landscapes. Recent fieldwork in mountain rivers has shown that wood jams retain significantly more macroplastic than other emergent surfaces within river channels. Here, we experimentally verify these findings by tracking the deposition of 64 PET bottles after 52–65 days of transport in the mid-mountain Skawa River (Polish Carpathians) under low to medium flow conditions. Despite variations in river channel management and the resulting morphological patterns along the study reach, the majority (71.9%, n = 46) of tracked bottles were trapped by wood jams near the low-flow channel. The trapping efficiency was three times higher in the straight, regulated reach (14.8% per km) than in the highly sinuous, unregulated reach (4.5% per km). In the regulated reach, water inundations and wood jams are confined to a narrow zone near the low-flow channel, which may explain the high macroplastic trapping efficiency under low to medium flow conditions. In contrast, in the unmanaged, seminatural reach, where wood jams and water inundation occur over broader areas formed by extensive gravel bars, the trapping potential is lower under similar flow conditions. Previous observations showed that macroplastic deposition hotspots associated with wood jams predominantly form in wide, unmanaged river sections, where numerous jams are inundated during high flows. Our results detail this understanding, suggesting that under low to medium flows, macroplastic hotspots can also form on wood jams in regulated, narrow reaches. These findings suggest that the occurrence of wood jams, channel morphology and past flow conditions are key predictors of macroplastic hotspots formation in mountain rivers.